Upaya Meningkatan Hasil Belajar Matematika Siswa dengan Model Discovery Learning pada Siswa Kelas XII Akuntansi SMK Swasta Bhakti Luhur - Yumihati Wau (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
The aim of this research is to determine whether the application of the Discovery Learning learning model can improve student learning outcomes at Bhakti Luhur Private Vocational School for the 2022/2023 academic year. This research is Classroom Action research which was carried out in two cycles with 8 meetings, with the research subjects being class XII Accounting students at Bhakti Luhur Private Vocational School, totaling 20 students. The instrument is a test consisting of 5 questions. The results of observations on learning outcomes obtained by applying the discovery learning learning model reached 68%, namely. 8 students out of 14 completed their studies. The results of the observation of the second comprehensive learning results reached 76%, namely. 11 of 14 students completed their studies. Based on the results of cycles I and II, it was concluded that the application of the Discovery Learning learning model could improve student learning outcomes at Bhakti Luhur Private Vocational School for the 2022/2023 academic year.